Heritability and its uses - Speed, Doug (Henry Stewart Talks, 2016)
The concept of heritability, How to measure heritability based on pedigree information, How to measure heritability from genetic (SNP) data, How SNP-based heritability analysis can be used to improve our understanding of complex traits.